2016
DOI: 10.1002/jbm.a.35947
|View full text |Cite
|
Sign up to set email alerts
|

Effect of matrix metalloproteinase‐mediated matrix degradation on glioblastoma cell behavior in 3D PEG‐based hydrogels

Abstract: Glioblastoma (GBM) is the most common and aggressive form of primary brain tumor with median survival of 12 months. To improve clinical outcomes, it is critical to develop in vitro models that support GBM proliferation and invasion for deciphering tumor progression and screening drug candidates. A key hallmark of GBM cells is their extreme invasiveness, a process mediated by matrix metalloproteinase (MMP)-mediated degradation of the extracellular matrix. We recently reported the development of a MMP-degradable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…In a separate study using the same material platform, but with thiolated hyaluronic acid that can be chemically conjugated to the matrix, the gel stiffness was maintained between 1.2 and 2.0 kPa but the degradability of the matrix was adjusted by varying the ratio of MMP-degradable crosslinker peptide to PEG-di-thiol. [66] They observed that U87 cells in degradable matrices (50% or 100% degradable crosslinker) exhibited a spread morphology and actin-dense structures extending into the surrounding gel, while cells in the non-degradable gels maintained a round morphology. [66] Interestingly, cells in all gels exhibited increased expression of MMP-1 and MMP-9 as well as significantly increased expression of hyaluronic acid synthase 2 compared with pre-encapsulation levels, but the differences in MMP and hyaluronic acid synthase expression between gels of different levels of degradability were not significant.…”
Section: Biomaterials For 3d Cell Biology Prospective Articlementioning
confidence: 99%
See 1 more Smart Citation
“…In a separate study using the same material platform, but with thiolated hyaluronic acid that can be chemically conjugated to the matrix, the gel stiffness was maintained between 1.2 and 2.0 kPa but the degradability of the matrix was adjusted by varying the ratio of MMP-degradable crosslinker peptide to PEG-di-thiol. [66] They observed that U87 cells in degradable matrices (50% or 100% degradable crosslinker) exhibited a spread morphology and actin-dense structures extending into the surrounding gel, while cells in the non-degradable gels maintained a round morphology. [66] Interestingly, cells in all gels exhibited increased expression of MMP-1 and MMP-9 as well as significantly increased expression of hyaluronic acid synthase 2 compared with pre-encapsulation levels, but the differences in MMP and hyaluronic acid synthase expression between gels of different levels of degradability were not significant.…”
Section: Biomaterials For 3d Cell Biology Prospective Articlementioning
confidence: 99%
“…[66] They observed that U87 cells in degradable matrices (50% or 100% degradable crosslinker) exhibited a spread morphology and actin-dense structures extending into the surrounding gel, while cells in the non-degradable gels maintained a round morphology. [66] Interestingly, cells in all gels exhibited increased expression of MMP-1 and MMP-9 as well as significantly increased expression of hyaluronic acid synthase 2 compared with pre-encapsulation levels, but the differences in MMP and hyaluronic acid synthase expression between gels of different levels of degradability were not significant. In addition, gene expression levels in these gels, normalized to pre-encapsulated gene expression, were similar to the soft gels of the previous study.…”
Section: Biomaterials For 3d Cell Biology Prospective Articlementioning
confidence: 99%
“…Hydrogels are often photo-crosslinked through chain-growth polymerization of acrylates [ 44 , 45 ]. More recently, thiol–ene photoreactions (e.g., between thiol and norbonene groups) have gained popularity [ 163 , 166 ]. Thiol–ene reactions proceed by step-growth polymerization, which yield hydrogels with more defined networks and fewer defects than those produced by chain-growth polymerization [ 170 ].…”
Section: Bioengineered Ex Vivo Models Of Gbmmentioning
confidence: 99%
“…To mimic the biochemical composition of the native brain and GBM tumor microenvironment, 3D hydrogel scaffolds have been fabricated from a variety of ECM-derived biopolymers, including HA [ 44–45 , 147 , 163–164 , 172 ], chitosan [ 158 , 165 ] and chondroitin sulfate [ 167 ] polysaccharides, and collagen/gelatin proteins [ 44–45 , 157 , 162 , 167 , 172 ]. As the ECM in the CNS contains high amounts of GAGs and few fibrous proteins like collagen I, many researchers have used HA-based hydrogels to mimic native brain.…”
Section: Bioengineered Ex Vivo Models Of Gbmmentioning
confidence: 99%
See 1 more Smart Citation